Negotiator: proposte a Quint. Decl. 320 Them. - Marchionni, Roberta (Rivista di Filologia e di Istruzione Classica, 2018)
Abstract From Ritter (1884) to Winterbottom (1984) the editors of Quintilian’s Minor Declamations have tried to emend the theme of decl. 320. This paper presents some new possibilities of emendation suggested by my work on the lemma negotiator at the Thesaurus linguae Latinae.